Immunomodulatory effect of marine lipids on food allergy - Abril, Ana G.; Carrera, Mónica; Pazos, Manuel (Frontiers in Nutrition, 2023)
Seafood is highly enriched in n-3 long-chain polyunsaturated fatty acids (n-3 LCPUFAs), particularly eicosapentaenoic acid (EPA, 20:5 n-3) and docosahexaenoic acid (DHA, 22:6 n-3), in contrast to the ultra-processed foods included in the modern Western diet that have high levels of n-6 linoleic acid (LA, 18:2 n-6), precursor for the pro-inflammatory n-6 arachidonic acid (ARA, 20:4 n-6). The capacity of marine lipids to reduce plasmatic triglycerides and blood pressure have been well-described. Moreover, recent studies have also raised evidence of a potential regulatory action of marine lipids on inflammation, the immune system, and food allergy (FA). FA is considered one of the main concerns to become life threatening in food safety. The prevalence of this emerging global problem has been increasing during the last two decades, especially in industrialized countries. About a 6-8% of young children and 2-4% of adults is estimated to be affected by FA. The main objective of the current study is to update the existing knowledge, but also the limitations, on the potential impact of marine lipids and their lipid mediators in regulating immunity, inflammation, and ultimately, food allergies. In particular, the focus is on the effect of marine lipids in modulating the key factors that control the sensitization and effector phases of FA, including gut microbiota (GM), inflammation, and immune system response. Results in animal models highlight the positive effect that consuming marine lipids, whether as a supplement or through seafood consumption, may have a relevant role in improving gut dysbiosis and inflammation, and preventing or reducing the severity of FA. However, more systematic studies in humans are needed to optimize such beneficial actions to each particular FA, age, and medical condition to reach an effective clinical application of marine lipids to improve FAs and their outcomes.